Microplastics in plastic bottle recycling and textile manufacturing wastewater: characterization and removal using ultrafiltration membranes - Q. N. Siew; W. J. Lau; S. Sethupathi; L. C. Sim; J.-J. Jiang; S. O. Lai; S. H. Shuit; G. Issabayeva; W. C. Chong (International Journal of Environmental Science and Technology, 2026)

Functional definition of endothelial progenitors by PROCR and PDGFRA co-expression - Cassandra Styke; Simranpreet Kaur; Seen-Ling Sim; Jilai Zhao; Chenhao Zhou; Ho Yi Wong; Jatin Patel; Edwige Roy; Mervyn C. Yoder; Richard P. Harvey; Abbas Shafiee; Kiarash Khosrotehrani (Angiogenesis, 2026)
The functional and molecular definition of progenitors giving rise to blood vessel endothelium in vivo remains disputed. Upon investigating the overlap of seemingly divergent reports currently defining putative endothelial progenitor cells (EPCs) using single-cell RNA-sequencing and flow cytometry, Protein C Receptor (PROCR) and Platelet-Derived Growth Factor Receptor Alpha (PDGFRA) largely overlapped with previously characterized murine aorta’s CD34 + CD31 low endovascular progenitors (EVPs). Functional assays and lineage tracing in homeostatic aorta and excisional wounds demonstrated increased clonogenic capacity, engraftment potential, and ability to form differentiated endothelial (D) cells of PROCR + PDGFRA + EPCs, termed as refined endothelial progenitor cell (rEPC), as compared to PROCR neg PDGFRA neg EVPs. Similar PROCR and PDGFRA expression in normal human aorta, and increased clonogenic capacity of CD34 + CD31 low PROCR + endothelial cells from freshly isolated human term placenta were observed as compared to controls. Functional validation of human rEPCs is supported by PROCR enrichment, while PDGFRA co‑expression in human endothelial progenitor–like cells is supported at the transcriptomic level only. Thus, overlapping PROCR and PDGFRA expression in EVPs narrows the population with true functional progenitor capacity.

Bacillus thuringiensis contamination as a biological hazard to embryogenesis of Carcinoscorpius rotundicauda in Malaysian tropical coasts - Rasha Ahmed Moqbel Ghaleb; Sim Sze Wei; Harris C. Raj Kumar; Nurul Huda Abdul Kadir; Hassan I. Sheikh; Lusita Meilana; Siti Nordahliawate Mohamed Sidique; Sivachandran Parimannan; Jayaraj Vijaya Kumaran; Bryan Raveen Nelson (Marine Environmental Research, 2026)

Ranking primary food allergens by specific IgE-binding and clinical relevance in Dutch adults to identify reference protein sets for allergenicity assessment - Sim Ray Yue; Michelle C.L. Chou; Emily J.J. Kallen; André C. Knulst; Geert F. Houben; Katrine Lindholm Bøgh; Thuy-My Le; Kitty C.M. Verhoeckx (Food and Chemical Toxicology, 2026)

Demography and Localized Reservoirs of Diversity Underlie Global Divergence in the Giant Kelp Macrocystis pyrifera - E. C. Giles; A. Zaiko; H. G. Hampton; P. Saenz‐Agudelo; M. Scriver; D. Crossett; A. Sim; X. B. Zhang; T. Jedrecka; C. O. Blain; L. Rauhina‐August; C. E. Cornwall; et al. (Molecular Ecology, 2026)
Accurate assessments of genetic diversity are crucial for effective management of natural resources. Numerous evolutionary mechanisms and genetic constraints can shape lineage divergence, challenging our quantification of biodiversity. Here, using whole genome resequencing of globally distributed giant kelp, Macrocystis pyrifera (Order: Laminariales), we show clear separation of genetic groups across the Pacific based on 99 genotyped individuals and 799,160 SNPs. Additionally, divergence across 88 genotyped individuals (53 derived in silico and 35 newly sequenced) considering 5,466,408 SNPs is attributed to both historical demographic processes and differential selection. Between Central California and the South Pacific (Chile, Tasmania, New Zealand), high divergence has occurred with very weak levels of gene flow, with concurrent timing of divergence. In parts of the South Pacific, kelp exhibited nucleotide diversity comparable to Central Californian populations but showed stronger signals of directional selection and excesses of rare alleles, with fewer genes showing signs of negative selection and some carbon‐related genes under positive selection. In contrast, Central Californian kelp had an excess of genes with synonymous mutations and showed evidence of a recent population contraction, as indicated by linkage disequilibrium and Tajima's D . In all populations, genome‐wide background divergence was paired with narrow genomic intervals of high nucleotide diversity and high linkage disequilibrium, which predominantly contained pervasive repetitive sequences. These repetitive regions were larger and more often shared among genetic groups in the South Pacific. They also appear to harbour genes of unknown function and alleles at intermediate frequency, suggesting that giant kelp maintain reservoirs of diversity within linked repeats, and this phenomenon is more pronounced in South Pacific M. pyrifera . Overall, the discovery of differential selection and structural variation as key drivers of divergence points to underappreciated genomic mechanisms of adaptation in kelp. These results will be useful for informing efforts to enhance climate resilience by identifying the evolutionary potential underlying kelp forest adaptation in the future.

Machine learning derived abdominal aortic calcification is associated with physical frailty in community-dwelling adults: the UK Biobank Imaging Study - Abadi K. Gebre; Marion Mundt; Elsa Dent; James Webster; Afsah Saleem; Syed Zulqarnain Gilani; Yuandan Zhang; Cassandra Smith; Parminder Raina; John P. Kemp; William D. Leslie; John T. Schousboe; et al. (GeroScience, 2026)

Gut microplastics of two non-native freshwater fish species, Geophagus altifrons and Cichla orinocensis, in Singapore reservoirs - Xue Shen Teo; Kean Sim Lai; Jeffrey T. B. Kwik; Maxine A. D. Mowe; Darren C. J. Yeo (Aquatic Ecology, 2026)

Distribution and taxonomic composition of leptocephali and hydrographic structure from New Zealand to the South Equatorial Current - Michael J. Miller; Shun Watanabe; Robert Schabetsberger; Nioka Behan-Kitto; Grace F. Cawley; Niamh Smith; Alisha M. Gill; Alexandre Che-Pelicier; Juliet E. Saul; Abigail Sim; Therese C. Miller; Sajini Dissanayake; et al. (Regional Studies in Marine Science, 2026)

Unprecedented Burning in Tropical Peatlands During the 20th Century Compared to the Previous Two Millennia - Yuwan Wang; Ted R. Feldpausch; Graeme T. Swindles; Patrick Moss; Hamish A. McGowan; Thomas G. Sim; Paul J. Morris; Adam Benfield; Colin Courtney‐Mustaphi; David Wahl; Encarni Montoya; Esther Githumbi; et al. (Global Change Biology, 2026)
Tropical peatland wildfire incidence has risen in recent decades, driven by drainage for land use and intensified by severe droughts with global climate change. These disturbances have altered vegetation structure, disrupted ecosystem functioning, and increased carbon emissions, particularly in Southeast Asia. However, the long‐term history and characteristics of wildfires in tropical peatlands remain largely unknown. Here, we compiled fifty‐eight macro‐charcoal records from peatlands across the tropics, ranging from lowland forested to montane peatlands, to assess millennia‐scale changes and controlling factors of tropical peatland burning. We divided the datasets into four main sub‐regions: Neotropical, Afrotropical, Indomalayan and Australasian ecoregions to explore regional variability. Tropical peatlands had high burning levels between 0 and 850 ce , followed by a relatively low and stable period until a marked increase during the 20th century. The general trend in tropical peatland burning follows changes in global temperature, and climate variables that control the length and severity of drought events have a notable influence on peat burning before 1900 ce . During the 20th century, regional differences were observed, with declining fire trends in the Neotropical and Afrotropical regions and increasing fire trends in the Indomalayan and Australasian regions. This difference is likely attributable to human activities, and such intervention is also evident in palm swamps and hardwood swamps under similar wet, weakly seasonal climates. With the increase in anthropogenic pressures on peatlands and greater climate variability, future wildfires in peatlands are likely to become more frequent and widespread across all tropical ecoregions. Conservation and sustainable land‐use practices could be used to mitigate and control peatland burning and protect these carbon‐rich sinks.

Effect of Halamphora coffeaeformis supplementation in rice bran biofloc on the growth and survival of black tiger shrimp (Penaeus monodon) postlarvae - Mohd Ihsanuddin Ahmad; Muhammad Farhan Nazarudin; Hazwani Hanim Hasnan; Ninie Diana Baharuddin; Kamil Latif; Clement R. de Cruz; Murni Karim; Hui Teng Tan; Yam Sim Khaw; Jeffrey K. C. Lee; Ikhsan Natrah (Aquaculture International, 2025)

Non-respiratory health risks and mortality associated with fighting bushfires (wildfires): a systematic review - Asmare Gelaw; Win Wah; Deborah C. Glass; Malcolm R. Sim; Ryan Hoy; Janneke Berecki-Gisolf; Karen Walker-Bone (International Archives of Occupational and Environmental Health, 2025)
Background Bushfires (also known as wildland or forest fires) expose emergency responders to occupational hazards under exceptional circumstances. Whilst the health impacts of structural firefighting have been studied, less is known about the non-respiratory health impacts or risk of mortality amongst bush firefighters, who can be volunteers. More information about health risks is needed to generate effective prevention strategies. Objective To critically evaluate and synthesise the published evidence about the non-respiratory health risks and risk of mortality associated with bushfire fighting. Methods A systematic literature search was conducted in Medline, Scopus, and Embase to identify studies evaluating morbidity or mortality or associated risk factors among bushfire fighters. The quality of included studies was evaluated twice independently using a specific quality assessment tool. Results Twenty-seven studies were included. 11(41%) were assessed as moderate quality and 16(59%) as low quality. There is a growing body of evidence for adverse short-term impacts of bushfire fighting on mental health and injuries. Linkage studies showed that volunteer firefighters had lower mortality and cancer risk in their late forties compared to the general population. Conclusion Most studies relied on cross-sectional and retrospective designs without comparison groups, limiting the ability to draw robust conclusions. It is essential to conduct higher-quality research using prospective designs and longer-term follow-up to better understand the health outcomes of bushfire fighting, particularly given the anticipated increase in the frequency and severity of bushfires.

Systematic review of impacts of occupational exposure to wildfire smoke on respiratory function, symptoms, measures and diseases - Win Wah; Asmare Gelaw; Deborah C. Glass; Malcolm R. Sim; Ryan F. Hoy; Janneke Berecki-Gisolf; Karen Walker-Bone (International Journal of Hygiene and Environmental Health, 2025)

Impact of extreme bushfire seasons on rates of occupational injury and disease compensation claims in first responders - Win Wah; Janneke Berecki-Gisolf; Deborah C. Glass; Ryan F. Hoy; Malcolm R. Sim; Alex Collie; Karen Walker-Bone (International Archives of Occupational and Environmental Health, 2024)

Recurrent selection shapes the genomic landscape of differentiation between a pair of host‐specialized haplodiploids that diverged with gene flow - Ashleigh N. Glover; Vitor C. Sousa; Ryan D. Ridenbaugh; Sheina B. Sim; Scott M. Geib; Catherine R. Linnen (Molecular Ecology, 2024)
Understanding the genetics of adaptation and speciation is critical for a complete picture of how biodiversity is generated and maintained. Heterogeneous genomic differentiation between diverging taxa is commonly documented, with genomic regions of high differentiation interpreted as resulting from differential gene flow, linked selection and reduced recombination rates. Disentangling the roles of each of these non‐exclusive processes in shaping genome‐wide patterns of divergence is challenging but will enhance our knowledge of the repeatability of genomic landscapes across taxa. Here, we combine whole‐genome resequencing and genome feature data to investigate the processes shaping the genomic landscape of differentiation for a sister‐species pair of haplodiploid pine sawflies, Neodiprion lecontei and Neodiprion pinetum . We find genome‐wide correlations between genome features and summary statistics are consistent with pervasive linked selection, with patterns of diversity and divergence more consistently predicted by exon density and recombination rate than the neutral mutation rate (approximated by dS). We also find that both global and local patterns of F ST , d XY and π provide strong support for recurrent selection as the primary selective process shaping variation across pine sawfly genomes, with some contribution from balancing selection and lineage‐specific linked selection. Because inheritance patterns for haplodiploid genomes are analogous to those of sex chromosomes, we hypothesize that haplodiploids may be especially prone to recurrent selection, even if gene flow occurred throughout divergence. Overall, our study helps fill an important taxonomic gap in the genomic landscape literature and contributes to our understanding of the processes that shape genome‐wide patterns of genetic variation.

Transient energetic particles as the origin of the mid-infrared north polar hotspot of Jupiter - S.J. Kim; C.K. Sim; T.R. Geballe; Y.L. Yung; S. Miller; S. Lee; C. Tao (Icarus, 2023)

Nitrate: The Dr. Jekyll and Mr. Hyde of human health? - Catherine P. Bondonno; Liezhou Zhong; Nicola P. Bondonno; Marc Sim; Lauren C. Blekkenhorst; Alex Liu; Anjana Rajendra; Pratik Pokharel; Dorit W. Erichsen; Oliver Neubauer; Kevin D. Croft; Jonathan M. Hodgson (Trends in Food Science & Technology, 2023)

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

A multi-centre retrospective study of Nocardia speciation and antimicrobial susceptibility in Queensland, Australia - B. Z. Sim; L. Aaron; C. Coulter; J. Parkes-Smith; T. Badrick; K. May; M. Armstrong; S. Hendry; L. Sundac; L. Dang; J. Ho; J. Hanson; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Assessment of Lymphoma and Other Hematologic Malignancies Training Needs Among Radiation Oncology Residents: a Brief Report - Jenna M. Kahn; Joanna C. Yang; Joachim Yahalom; Bouthaina S. Dabaja; Neha Vapiwala; Bradford S. Hoppe; Yolanda D. Tseng; Chelsea C. Pinnix; Rahul R. Parikh; Austin J. Sim; John P. Plastaras; Jillian R. Gunther (Journal of Cancer Education, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Tropical macrophytes promote phytoplankton community shifts in lake mesocosms: relevance for lake restoration in warm climates - Darren Z. H. Sim; Maxine A. D. Mowe; Yiluan Song; Joy Lu; Hugh T. W. Tan; Simon M. Mitrovic; Daniel L. Roelke; Darren C. J. Yeo (Hydrobiologia, 2021)

Impact of formulary interventions on the minimum inhibitory concentration of methicillin-resistant Staphylococcus aureus to mupirocin, chlorhexidine, and octenidine in a Singapore tertiary institution - Shuwei Zheng; S. J. Chung; H. C. J. Sim; T. M. Chlebicka; Y. H. Chan; T. P. Lim; L. H. A. Kwa; M. P. Chlebicki (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Assessment of air purifier on efficient removal of airborne bacteria, Staphylococcus epidermidis, using single-chamber method - Jung Hoon Lee; Jeong Yup Kim; Bo-Bae Cho; J. R. Anusha; Ju Yong Sim; C. Justin Raj; Kook-Hyun Yu (Environmental Monitoring and Assessment, 2019)

Global Island Monitoring Scheme (GIMS): a proposal for the long-term coordinated survey and monitoring of native island forest biota - Paulo A. V. Borges; Pedro Cardoso; Holger Kreft; Robert J. Whittaker; Simone Fattorini; Brent C. Emerson; Artur Gil; Rosemary G. Gillespie; Thomas J. Matthews; Ana M. C. Santos; Manuel J. Steinbauer; Christophe Thébaud; et al. (Biodiversity and Conservation, 2018)

Trade-offs between defence and competition in gregarious juvenile fluted giant clams (Tridacna squamosa L.) - Darren Z. H. Sim; Mei Lin Neo; Ambert C. F. Ang; Lynette S. M. Ying; Peter A. Todd (Marine Biology, 2018)

Genome‐wide set of SNP s reveals evidence for two glacial refugia and admixture from postglacial recolonization in an alpine ungulate - Zijian Sim; Jocelyn C. Hall; Bill Jex; Troy M. Hegel; David W. Coltman (Molecular Ecology, 2016)
Past glaciation events have played a major role in shaping the genetic diversity and distribution of wild sheep in North America. The advancement of glaciers can isolate populations in ice‐free refugia, where they can survive until the recession of ice sheets. The major Beringian refugium is thought to have held thinhorn sheep ( Ovis dalli ) populations during times of glacial advance. While isolation in the major refugium can account for much of the genetic and morphological diversity seen in extant thinhorn sheep populations, mounting evidence suggests the persistence of populations in smaller minor refugia. We investigated the refugial origins of thinhorn sheep using ~10 000 SNP s obtained via a cross‐species application of the domestic sheep ovine HD BeadChip to genotype 52 thinhorn sheep and five bighorn sheep ( O. canadensis ) samples. Phylogenetic inference revealed a distinct lineage of thinhorn sheep inhabiting British Columbia, which is consistent with the survival of a group of thinhorn sheep in a minor refugium separate from the Beringian refugium. Isolation in separate glacial refugia probably mediated the evolution of the two thinhorn sheep subspecies, the white Dall's sheep ( O. d. dalli ), which persisted in Beringia, and the dark Stone's sheep ( O. d. stonei ), which utilized the minor refugium. We also found the first genetic evidence for admixture between sheep from different glacial refugia in south‐central Yukon as a consequence of post glacial expansion and recolonization. These results show that glaciation events can have a major role in the evolution of species inhabiting previously glaciated habitats and the need to look beyond established refugia when examining the evolutionary history of such species.

Recovery of the South Atlantic’s largest green turtle nesting population - Sam B. Weber; Nicola Weber; Jacqui Ellick; Andrew Avery; Robert Frauenstein; Brendan J. Godley; Jolene Sim; Natasha Williams; Annette C. Broderick (Biodiversity and Conservation, 2014)

Proof-of-concept randomized controlled trial of pregnenolone in schizophrenia - Christine E. Marx; Jimmy Lee; Mythily Subramaniam; Attilio Rapisarda; Dianne C. T. Bautista; Edwin Chan; Jason D. Kilts; Robert W. Buchanan; Eu Pui Wai; Swapna Verma; Kang Sim; Jayaraman Hariram; et al. (Psychopharmacology, 2014)

Conservation of Portuguese red-listed bryophytes species in Portugal: Promoting a shift in perspective on climate changes - C. Sérgio; C. A. Garcia; C. Vieira; H. Hespanhol; M. Sim-Sim; S. Stow; R. Figueira (Plant Biosystems, 2014)

Snapper ( Chrysophrys auratus ): a review of life history and key vulnerabilities in New Zealand - DM Parsons; CJ Sim‐Smith; M Cryer; MP Francis; B Hartill; EG Jones; A Le Port; M Lowe; J McKenzie; M Morrison; LJ Paul; C Radford; et al. (New Zealand Journal of Marine and Freshwater Research, 2014)
Snapper ( Chrysophrys auratus ) is an important coastal fish species in New Zealand for a variety of reasons, but the large amount of research conducted on snapper has not been reviewed. Here, we review life history information and potential threats for snapper in New Zealand. We present information on snapper life history, defining stages (eggs and larvae, juvenile and adult), and assess potential threats and knowledge gaps. Overall we identify six key points: 1. post‐settlement snapper are highly associated with certain estuarine habitats that are under threat from land‐based stressors. This may serve as a bottleneck for snapper populations; 2. the largest knowledge gaps relate to the eggs and larvae. Additional knowledge may help to anticipate the effects of climate change, which will likely have the greatest influence on these early life stages; 3. ocean acidification, from land‐based sources and from climate change, may be an important threat to larval snapper; 4. a greater understanding of population connectivity would improve certainty around the sustainability of fishery exploitation; 5. the collateral effects of fishing are likely to be relevant to fishery productivity, ecosystem integrity and enduser value; 6. our understanding of the interrelationships between snapper and other ecosystem components is still deficient.

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Comparison of phenotypic methods and matrix-assisted laser desorption ionisation time-of-flight mass spectrometry for the identification of aero-tolerant Actinomyces spp. isolated from soft-tissue infections - L. S. Y. Ng; J. H. C. Sim; L. C. Eng; S. Menon; T. Y. Tan (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Quantifying global greenhouse gas emissions from land‐use change for crop production - Helen C. Flynn; Llorenç Milà i. Canals; Emma Keller; Henry King; Sarah Sim; Astley Hastings; Shifeng Wang; Pete Smith (Global Change Biology, 2012)
Many assessments of product carbon footprint ( PCF ) for agricultural products omit emissions arising from land‐use change ( LUC ). In this study, we developed a framework based on IPCC national greenhouse gas inventory methodologies to assess the impacts of LUC from crop production using oil palm, soybean and oilseed rape as examples. Using ecological zone, climate and soil types from the top 20 producing countries, calculated emissions for transitions from natural vegetation to cropland on mineral soils under typical management ranged from −4.5 to 29.4 t CO 2 ‐eq ha −1 yr −1 over 20 years for oil palm and 1.2–47.5 t CO 2 ‐eq ha −1 yr −1 over 20 years for soybeans. Oilseed rape showed similar results to soybeans, but with lower maximum values because it is mainly grown in areas with lower C stocks. GHG emissions from other land‐use transitions were between 62% and 95% lower than those from natural vegetation for the arable crops, while conversions to oil palm were a sink for C . LUC emissions were considered on a national basis and also expressed per‐tonne‐of‐oil‐produced. Weighted global averages indicate that, depending on the land‐use transition, oil crop production on newly converted land contributes between −3.1 and 7.0 t CO 2 ‐eq t oil production −1 yr −1 for palm oil, 11.9–50.6 t CO 2 ‐eq t oil production −1 yr −1 for soybean oil, and 7.7–31.4 t CO 2 ‐eq t oil production −1 yr −1 for rapeseed oil. Assumptions made about crop and LUC distribution within countries contributed up to 66% error around the global averages for natural vegetation conversions. Uncertainty around biomass and soil C stocks were also examined. Finer resolution data and information (particularly on land management and yield) could improve reliability of the estimates but the framework can be used in all global regions and represents an important step forward for including LUC emissions in PCF s.

Tree-pulling experiment: an analysis into the mechanical stability of rain trees - Lai Fern Ow; F. R. Harnas; I. G. B. Indrawan; A. Sahadewa; E. K. Sim; H. Rahardjo; E. C. Leong; Y. K. Fong; P. Y. Tan (Trees, 2010)

Linkage disequilibrium between the CYP2C19*17 allele and wildtype CYP2C8 and CYP2C9 alleles: identification of CYP2C haplotypes in healthy Nordic populations - Rasmus S. Pedersen; Charlotte Brasch-Andersen; Sarah C. Sim; Troels K. Bergmann; Jónrit Halling; Maria S. Petersen; Pál Weihe; Hege Edvardsen; Vessela N. Kristensen; Kim Brøsen; Magnus Ingelman-Sundberg (European Journal of Clinical Pharmacology, 2010)

Increased P2X7R expression in atrial cardiomyocytes of caveolin-1 deficient mice - K. Barth; C. Pfleger; A. Linge; J. A. Sim; A. Surprenant; N. Steinbronn; R. H. Strasser; M. Kasper (Histochemistry and Cell Biology, 2010)

Molecular genetics and epigenetics of the cytochrome P450 gene family and its relevance for cancer risk and treatment - Cristina Rodriguez-Antona; Alvin Gomez; Maria Karlgren; Sarah C. Sim; Magnus Ingelman-Sundberg (Human Genetics, 2010)

Relationship between cardiopulmonary mortality and cancer risk and quantitative exposure to polycyclic aromatic hydrocarbons, fluorides, and dust in two prebake aluminum smelters - Melissa C. Friesen; Geza Benke; Anthony Del Monaco; Martine Dennekamp; Lin Fritschi; Nick de Klerk; Jan L. Hoving; Ewan MacFarlane; Malcolm R. Sim (Cancer Causes & Control, 2009)

Kinetics of omeprazole and escitalopram in relation to the CYP2C19*17 allele in healthy subjects - Staffan Ohlsson Rosenborg; Jessica Mwinyi; Maria Andersson; R. Michael Baldwin; Rasmus Steen Pedersen; Sarah C. Sim; Leif Bertilsson; Magnus Ingelman-Sundberg; Erik Eliasson (European Journal of Clinical Pharmacology, 2008)

Identification of random amplified polymorphic DNA (RAPD) marker for differentiating male from female and sporophytic thalli of Gracilaria changii (Rhodophyta) - M. C. Sim; P. E. Lim; S. Y. Gan; S. M. Phang (Journal of Applied Phycology, 2007)

QTL mapping of resistance to gray leaf spot in ryegrass - J. Curley; S. C. Sim; S. Warnke; S. Leong; R. Barker; G. Jung (Theoretical and Applied Genetics, 2005)

Genetic linkage mapping of an annual × perennial ryegrass population - S. E. Warnke; R. E. Barker; Geunhwa Jung; Sung-Chur Sim; M. A. Rouf Mian; M. C. Saha; L. A. Brilman; M. P. Dupal; J. W. Forster (Theoretical and Applied Genetics, 2004)

Molecular evolutionary analysis of the widespread piggyBac transposon family and related "domesticated" sequences - A. Sarkar; C. Sim; Y. S. Hong; J. R. Hogan; M. J. Fraser; H. M. Robertson; F. H. Collins (Molecular Genetics and Genomics, 2003)

Construction of a BAC library and generation of BAC end sequence-tagged connectors for genome sequencing of the African malaria mosquito Anopheles gambiae - Y. S. Hong; J. R. Hogan; X. Wang; A. Sarkar; C. Sim; B. J. Loftus; C. Ren; E. R. Huff; J. L. Carlile; K. Black; H.-B. Zhang; M. J. Gardner; et al. (Molecular Genetics and Genomics, 2003)

Regulation of desmosomal cell adhesion in human tumour cells by polyunsaturated fatty acids - Wen G. Jiang; Sim K. Singhrao; Stephen Hiscox; Maurice B. Hallett; Richard P. Bryce; David F. Horrobin; Malcolm C. A. Puntis; Robert E. Mansel (Clinical & Experimental Metastasis, 1997)

Mapping the bovine factor H gene to Chromosome 16 by SSCP analysis - J. L. Williams; D. H. Lester; V. M. Teres; W. Barendse; R. B. Sim; C. J. Soames (Mammalian Genome, 1997)

Linear and nonlinear stiffness and friction in biological rhythmic movements - P. J. Beek; R. C. Schmidt; A. W. Morris; M. -Y. Sim; M. T. Turvey (Biological Cybernetics, 1995)